DUNIA ABSURD DAN PERLAWANAN KELAS PADA DRAMA DAG-DIG-DUG KARYA PUTU WIJAYA - Yasa, I Nyoman (Lingua Didaktika: Jurnal Bahasa dan Pembelajaran Bahasa, 2010)
Research on drama in Indonesia is an effort to apply and express the theory in Indonesia. Naturally a theory existence from research accumulation to applied skills. It is hoped that this research can accumulate the science, mainly drama. The term of absurd was used by Martin Esslin for kind of theater that used the failure of language as main of communication. Besides, this term is popularized by Eugene Ionesco. He is a writer of absurd theater. Many of his drama already translated and performed in Indonesia. The data that already collected is analyzed by using the concept of absurdity to reveal the absurdity in Dag-Dig-Dug drama. In other side, the concept of class from Karl Marx is used to comment the domination and class resistance that are taken from Dag-Dig-Dug drama. Dag-Dig-Dug shows the social problems, mainly domination and hegemony of powerful person toward proletarian people. The domination and hegemony are in form of physics and psychology.